Models of Analysis of the European Commission Leadership - Farcas, Raluca (European Scientific Journal, ESJ, 2020)
This paper aims to analyze the leadership models of the European Commission in terms of the function of setting the agenda of the European Union and in terms of political leadership. In this context, at the European level leadership is shared between several actors, making it difficult for the European Commission to exercise leadership traditionally, mostly for its lack of direct decision-making powers. Thus, the most relevant political roles of the President of the European Commission are to set the European agenda and to persuade and influence the other stake-holders to follow his directions for deepening European integration. In this regard, the article comparatively analyzes the leadership of Jacques Delors, Jean-Claude Juncker, and Ursula von der Leyen to identify the leadership model proposed at the beginning of their term, and to what extent, they exercised a political role. The tools used in the analysis are the inaugural speeches and the following three variables: how they organized the Commission to strengthen the political role of the President, how they mobilized resources from the other institutions of the European Union, and the formation of coalitions and networks. The article concluded that the leadership model proposed by Ursula von der Leyen falls within the supranational pattern of Delors’ time, moving away from the model of political leadership proposed by Juncker. The accuracy of the research is limited by the fact that Ursula von der Leyen is only in her first year as President of the European Commission.